Sistrunk Procedure on Malignant Thyroglossal Duct Cyst - Diani Kartini; Sonar S. Panigoro; Agnes S. Harahap (Case Reports in Oncological Medicine)
A thyroglossal duct cyst is a lesion that occurs as a result from failure of the thyroglossal duct to obliterate during fetal development. Malignant progression is a rare event that might occur in less than 1% of all cases. Because of its rarity, there are conflicting opinions regarding the management of the case. In the present study, a 46-year-old male presented with a painless neck mass that had increased in size over the last 6 months. There was no difficulty in swallowing and breathing, change in voice, significant weight loss, or any signs of hyperthyroidism. Laboratory workup showed that results were within normal limits. Thyroid gland ultrasonography and cervical contrast CT scan revealed a complex cystic mass that pointed towards a thyroglossal duct cyst. We performed Sistrunk procedure. Postoperative pathology examination revealed microscopic appearance of the thyroglossal duct cyst with a classic follicular variant of papillary thyroid carcinoma. Our latest follow-up showed no signs of tumor recurrence or any complications following surgery on locoregional status. As a fine needle aspiration biopsy cannot ensure a precise result in all of cases, it is essential to perform a solid physical examination and thorough supporting examination in deciding the precise management for the patient.